The Jewish Youth in Times of Political Radicalization : Argentina, 1960/1970 - Kahan, Emmanuel Nicolás (2022)
Although the Six-Day War in June 1967 was neither the first nor the most relevant violent outbreak in the Arab-Israeli conflict, it was extensively treated in Argentine public debates and widely analyzed as an exceptional event. As different works on Jewish life in Argentina have shown, the country's Jewish presence during the first half of the twentieth century was primarily challenged by right-wing nationalist organizations. This situation changed during the 1960s and especially after the June War. In its aftermath, the debates began circling around the legitimacy of the State of Israel and Zionism and a growing number of the discussions' participants belonged to different sections of the national left. This article aims to reveal how these years were perceived by some of Argentina's most outstanding intellectuals - Abelardo Castillo, José Itzigsohn, Emilio Troise, León Perez, Pedro Orgambide, Horacio Verbitsky, Alfredo Varela, and León Rozitchner - and how they developed their dissimilar views on the State of Israel. It also intends to show how a spatially distant war served to formulate their positions on international politics as well as to situate themselves in the local political agenda. Finally, the article seeks to sharpen the understanding of the tensions this outbreak in the Arab-Israeli conflict generated between the organizations of the national left and the different protagonists of Jewish life in Argentina.
Keywords: Jewish; Argentina; Youth; Radicalization